Evidence for phloem loading via the abaxial bundle sheath cells in maize leaves. Issue 3 (7th January 2021) - Bezrutczyk, Margaret; Zöllner, Nora R; Kruse, Colin P S; Hartwig, Thomas; Lautwein, Tobias; Köhrer, Karl; Frommer, Wolf B; Kim, Ji-Yun
Abstract : Maize appears to use a previously undescribed phloem loading mechanism, in which abaxial bundle sheath cells export sucrose to transfer it to the vasculature. Abstract: Leaves are asymmetric, with different functions for adaxial and abaxial tissue. The bundle sheath (BS) of C3 barley ( Hordeum vulgare ) is dorsoventrally differentiated into three types of cells: adaxial structural, lateral S-type, and abaxial L-type BS cells. Based on plasmodesmatal connections between S-type cells and mestome sheath (parenchymatous cell layer below bundle sheath), S-type cells likely transfer assimilates toward the phloem. Here, we used single-cell RNA sequencing to investigate BS differentiation in C4 maize ( Zea mays L. ) plants. Abaxial BS ( ab BS) cells of rank-2 intermediate veins specifically expressed three SWEET sucrose uniporters (SWEET13a, b, and c) and UmamiT amino acid efflux transporters. SWEET13a, b, c mRNAs were also detected in the phloem parenchyma (PP). We show that maize has acquired a mechanism for phloem loading in which ab BS cells provide the main route for apoplasmic sucrose transfer toward the phloem. This putative route predominates in veins responsible for phloem loading (rank-2 intermediate), whereas rank-1 intermediate and major veins export sucrose from the PP adjacent to the sieve element companion cell complex, as in Arabidopsis thaliana . We surmise that ab BS identity is subject to dorsoventral patterning and has components of PP identity. These observations provide insights into the unique transport-specific properties of ab BS cells and support a modification to the canonical phloem loading pathway in maize.